Future impact of thymoquinone-loaded nanoemulsion in rabbits: prospects for enhancing growth, immunity, antioxidant potential and resistance against Pasteurella multocida - Abd El-Hamid, Marwa I.; El-Azzouny, Mona M.; El-Malt, Rania M. S.; Elkenawy, Mona E.; Abdelwarith, Abdelwahab A.; Younis, Elsayed M.; Youssef, Wessam; Dawod, Rehab E.; Elged, Dalia W. A. H.; Habaka, Manal A. M.; El Oksh, Amal S. A.; Mekawy, Soad; et al. (Frontiers in Veterinary Science, 2024)
Phytochemical nanoemulsions, such as thymoquinone nanoemulsions (TQN), are regarded as innovative alternatives to antimicrobials that significantly improve the performance, digestion, antioxidant potential and immunity of rabbits. Thus, the potential effects of TQN on growth, digestibility, antioxidant potential, immunity and resistance against Pasteurella multocida (P. multocida) in rabbits were assessed. Herein, 240 rabbits were offered either a basal diet or diets fortified with three TQN-graded concentrations. At 60 days of age, rabbits were challenged with multidrugresistant (MDR) virulent P. multocida strain. Our outcomes described that dietary inclusion of TQN, especially at higher concentrations, significantly enhanced the growth performance of rabbits, which was supported by increasing the levels of jejunal lipase, amylase and trypsin enzymes. Of note, the levels of muscle and jejunal antioxidant enzymes [superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT) and total antioxidant capacity (T-AOC)], serum immunological markers (IgG, IgG, IgM and total Igs) and blood phagocytic percentage were significantly provoked after TQN fortification; meanwhile, the levels of muscle and jejunal MDA, serum biochemical parameters (total cholesterol, TG and LDL), abdominal fat percentage, breast and thigh cholesterol were significantly decreased following TQN supplementations. Our findings showed that TQN protected rabbits against P. multocida experimental challenge as evidenced by reducing P. multocida counts in rabbits' lungs, downregulating the transcription levels of P. multocida virulence-related genes (ptfA, toxA and nanB) at 48 and 96 h post-infection and ameliorating the expression levels of cytokines-related genes (IL-1β, IL-10, IL-8, IL-6, DEFB1, TNF-α, TLR-4 and TLR-2) at 96 h post-infection. Our findings suggest the utilization of TQN in rabbits` diets due to their stimulating effects on digestibility as well as their growth-promoting, anti-inflammatory, antioxidant, antibacterial, anti-virulence and immunostimulant properties, which enhance the rabbits` P. multocida resistance.